Profile of oral manifestations, oral hygiene, and nutritional status in pregnant women - Hidayat, Wahyu; Pribadi, Indra Mustika Setia; Zakiawati, Dewi; Suwargiani, Anne Agustina (Universitas Padjadjaran, 2019)
Introduction: The pregnancy condition leads to few changes in women’s bodies, such as hormonal, physiological, and diet. These changes also manifest in dental and oral health. Hormonal changes affect the susceptibility of oral mucosal tissue, whereas emotional and dietary changes alter the pattern of dietary intake, dental cleaning, oral hygiene, and nutritional status. The purpose of this study was to discover the profile of oral manifestations, oral hygiene, and nutritional status in pregnant women. Methods: The population of the study was the pregnant women who visited the Garuda Community Health Centre in Bandung. Subjects were pregnant women aged 17-43 years old. The samples must meet the inclusion criteria of good health status, and the exclusion criteria were no systemic abnormalities, and not currently under long-term antibiotic therapy. The research design was a cross-sectional observation. Indicators measured in this survey were the profiles of oral manifestations, oral hygiene status which assessed using OHI-S, and nutritional status of pregnant women using haemoglobin (Hb) and Body Mass Index (BMI) level. Results: Oral manifestations found in pregnant women were tongue disorders and ulceration, with the coated tongue as the most frequently detected manifestation, and the least found was recurrent aphthous stomatitis, whereas the oral hygiene of pregnant women was categorised as good in the 1st and 2nd-trimester of pregnancy. However, it was found to be moderate in the 3rd trimester. In respect of the Hb level, the nutritional status of the pregnant women was averagely good. By contrast, the BMI score revealed that pregnant women was found of having overweight during the 2nd and 3rd trimester. Conclusion: The most frequently found oral manifestation in pregnant women is coated tongue, while the oral hygiene is categorised as good on the first two trimesters, and the nutritional status in the last two trimesters is considered as overweight.Keywords: Oral manifestation, oral hygiene, nutritional status.